The Slow Road from Serfdom: Labor Coercion and Long-Run Development in the Former Russian Empire - Buggle, Johannes C.; Nafziger, Steven (The Review of Economics and Statistics, 2021)
This paper examines the long-run economic consequences of Russian serfdom. Employing data on the intensity of labor coercion just prior to emancipation in 1861, we document that a 25 percentage point increase in historical serfdom (1 SD) reduces household expenditure today by up to 17%. We then provide evidence on the persistence of this relationship by studying city populations over the period 1800 to 2002. Exploring mechanisms, our findings suggest that less urban agglomeration and slower industrial development in areas with a greater degree of serfdom perpetuated the negative effects of forced labor before, during, and after the Soviet period.